Does being physically active and engaged affect reading ability? A review of the literature - Yohanes Gatot Sutapa Yuliana; Isti Dwi Puspita Wati; Amriani Amir; Mimi Haetami; Albadi Sinulingga; I Gusti Putu Ngurah Adi Santika; Asry Syam; Rezza Dewintha; Cahniyo Wijaya Kuswanto (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Reading ability is one of the basic skills to open the horizons of knowledge and bring authentic input for a performance of the mind. Learning programs in higher education are aimed at equipping students to have comprehensive critical thinking-based reading skills. Learning to read is an abstract process of cognition which is the performance of the sense of sight, a cognitive process consisting of critical thinking and self-awareness elaboration. It is suspected that students who are active will have better speed in reading comprehension. This research aims to examine based on research evidence by reviewing the literature. Materials were searched using the keywords "physical activity to reading skill". Searches were conducted in Scopus and PubMed accounts. Based on the analysis step using PRISMA, 13 relevant articles were finally obtained in accordance with the purpose of writing. Based on this study and review, it can be concluded that physical activity can be in the form of walking, cycling, play programs, gross motor interventions, providing motor stimulation to the whole body, has a positive effect on reading ability. The positive results of physical activity are the acquisition of fine and gross motor skills, the achievement of a good level of fitness that bridges the enthusiasm and endurance of learning so that it affects reading skills. The second conclusion from this study, besides specifically affecting reading skills, is also evidenced by 7 articles mentioning activity, activeness and the results of these two things affecting academic achievement.